Shift in Theme-Rheme on Translation The Disyinction of Kawitan Temple Systemic Functional Linguistics Perspective - Bratayadnya, Putu Agus; Suparwa, I Nyoman; Satyawati, Made Sri (e-Journal of Linguistics; Vol 15 No 2 (2021): e-jl July, 2021)
Translation text has very important role in tourism market since Bali become very popular in tourism world.  One of translation text used as media for Bali tourism promotions is Why Bali is Known as ”The Island of Thousand Temples”. The text is written in two languages, namely English as the source language and Indonesian as the target language. There are several differences between the source and the target languages in formulating language as message. Such differences were analyzed from systemic functional linguistics point view. The theory used to analyze is the theory of clause of message taken from Halliday. This is qualitative research, namely by approaching the theory clause as message, theme and rheme.  Themes of the clauses used in both of texts were compared and analyzed. The result of the research suggested that topical themes were mostly used in the source language, while textual theme was also found in the target language. The themes used in the target language get shifts which resulted to loss and again. The phenomenon causes between the source and the target gets far from equivalence which makes the readers/listeners have different interpretation to the message of the clauses.